Properties of superplasticizer-amended superfine cement grouted sand - Mollamahmutog?lu, Murat; Avci, Eyübhan (Fundatia Serban Solacolu rev.romana.de.materiale@gmail.com, 2019)
The effect of superplasticizer on the grouting performance of superfine cement and the engineering properties of grouted sand were investigated. At first, the bleeding, setting time, and viscosity tests were conducted to determine the rheological characteristics of superfine cement grouts with or without superplasticizer at different water-cement ratios. Thereafter, the groutability of superfine cement grouts into various graded sand specimens with or without superplasticizer were tested. Those specimens grouted successfully were then subjected to unconfined compression tests at different time intervals. The addition of superplasticizer to superfine cement grouts increased their bleeding, initial and final setting times but decreased their viscosities. As the unconfined compressive strength (UCS) of superfine cement grouted sand specimens increased with the addition of superplasticizer. It was shown that the engineering properties of superfine cement grouted sand specimens were better improved with the addition of superplasticizer. © 2019, Fundatia Serban Solacolu. All rights reserved.
Keywords: Groutability; Permeability; Superfine cement; Superplasticizer; Unconfined compressive strength